Subacute Combined Degeneration of the Spinal Cord Caused by Autoimmune Gastritis - Ota, Kazuhiro (Intern Med, 2020)
A 68-year-old woman presented with a 2-year history of worsening unsteady gait. Her neurological examination revealed peripheral neuropathy with lower limb sensory dominance. T2-weighted imaging revealed a disorder of the posterior cervical cord. Blood test findings revealed vitamin B(12) deficiency, and gastroscopy revealed typical findings of autoimmune gastritis. She received vitamin B(12) supplementation, but some peripheral neuropathy symptoms persisted due to longstanding vitamin B(12) deficiency. Asymptomatic patients should undergo gastroscopy to detect autoimmune gastritis, as chronic vitamin B(12) deficiency causes irreversible peripheral neuropathy.